Novice English Teachers’ Perceptions of English as an International Language: A Study of Private Sector Schools (Peshawar) - Sanjeeda Rehman; Muhammad Waqar Ali (University of Chitral Journal of Linguistics and Literature, 2023)
The study uses a quantitative research methodology to examine how in-service English teachers in Peshawar, Pakistan feel about L1 identity, Non-Native Speakers’ (NNS) English accents, language ownership, and the legitimacy of language usage by NNSs. Fifty in-service instructors were given a meticulously designed questionnaire that was organized around each variable adopted from different research studies (Curran & Chern, 2017; Ren et al., 2016; Rahatlou et al., 2018). Descriptive statistics including frequency, means, percentage, and standard deviations, are applied to the quantitative data to identify response dispersion and central patterns. There are differences in opinions regarding students learning English based on Native Speaker (NS) models, even if there is agreement that successful communication should come before native-like competency. The findings provide light on the intricate interactions between historical, cultural, and educational elements that shaped the perspectives of the participants. Kumaravadivelu (2012) highlights a multifaceted perspective formed by colonial legacies and internal and external constraints, as seen by the coexistence of varied perspectives on language ownership and pride in Non-native accents. Divergent perspectives on students acquiring English highlight the impact of learning environments.